Adóreform és központi árszabályozás a 3. század gazdasági krízisében : Diocletianus válasza az inflációs válságra - Jusztinger, János (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
The absolute monarchy established by Emperor Diocletian (284–305) naturally meant centralization in financial administration as well. Diocletian's fiscal reforms – which fit into these reorganizations – primarily served to consolidate the empire's economic power in a period of extreme crisis. Among the monarch’s several financial measures – in addition to the creation of a state monopoly on coinage – the tax reform of 301 can be considered the most determinative. In the same year, the emperor's provisions were supplemented by a special institution which clearly has a ‘crisis law character’ within the framework of free-market economy. The price maximization decree of Diocletian (Edictum de pretiis rerum venalium) was created specifically to solve or at least mitigate the economic crisis of the third century. While in previous centuries the value of Roman money was relatively constant, the main sign of the financial crisis of the time was precisely inflation. The aim of the study is to present the two most important elements of this comprehensive reform concept.